Advanced Operation and Maintenance in Solar Plants, Wind Farms and Microgrids - Hernández-Callejo, Luis; del Carmen Alonso García, Maria; Gallardo Saavedra, Sara (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint presents advances in operation and maintenance in solar plants, wind farms and microgrids. This compendium of scientific articles will help clarify the current advances in this subject, so it is expected that it will please the reader.